Influence of Ovo Injecting IGF-1 on Weights of Embryo, Heart and Liver of Duck During Hatching Stages - Wang, Guo-Song; Liu, He-He; Li, Lin-Seng; Wang, Ji-Wen (International Journal of Poultry Science, 2012)
IGF-1 is one of important factors which can make an effect on differentiation and development of tissues and organs. The present study was to observe the effects of IGF-1 to duck’s embryo, liver and heart’s development, by in ovo feeding IGF-1 to hatching duck eggs. Firstly, 0.5mL IGF-1 diluted in saline at different concentrations including 0, 80, 100 and 120ng/mL were injected into duck eggs and the results showed that 100ng/mL was the adjust concentration which had significant effects on duck embryo, liver and heart’s development in later periods of hatching stages comparing with the control group. Then, the adjusted concentration of IGF-1 was used to investigate the developmental roles of IGF-1 on duck embryo and organ’s development. The results showed that IGF-1 had a positive effect on duck embryonic development, especially had an obvious effect on liver. It was concluded that IGF-1 may play an important role in the process of duck liver development during the hatching stages.